An Analytical, Scholarly, and Critical Study of the Doctrines of the Zikri Faith: DOI:https://doi.org/10.5281/zenodo.17605535 (Khairulummah, 2025)
This research paper, titled “An Analytical, Scholarly, and Critical Study of the Doctrines of the Zikri Faith,” presents a comprehensive analytical study of the history, beliefs, social structure, and intellectual evolution of the Zikri sect, which originated in the Indian subcontinent, particularly in Balochistan. The main objective of this study is to critically and academically analyze the historical background of the Zikri religion, its political and religious factors, and its intellectual deviations from Islamic beliefs.The foundation of the Zikri sect was laid around the fifteenth century A.D., when its early followers began preaching their ideas in Makran and the coastal regions of Balochistan. From the very beginning, it deviated from its original Islamic spirit and adopted a distinct religious identity. Later, under the influence of the Bilidi and Gichki rulers, this sect also gained political stability.Abdul Ghani Baloch and Abdul Karim Dost have rejected this impression, declaring their religion to be a spiritual school within Islam that believes in monotheism, the Qur’an, prophethood, and the fundamental pillars of Islam. Regarding the deviant beliefs from Islam, it is stated that during the period of Mulla Murad Gichki, significant changes occurred in the fundamental doctrines of the Zikri faith, which transformed it into a new religious system distinct from traditional Islam.With detailed references, the paper makes it clear that in the early Zikri beliefs, Muhammad Mahdi Atki was elevated to the rank of Mahdi al-Akhir al-Zaman and even to the status of a prophet. Their specific creed — “La ilaha illallah, Noor Muhammad Mahdi Rasul Allah” — became prevalent, and there were clear deviations from Islamic teachings regarding prayer, fasting, pilgrimage, and the Qibla. However, contemporary Zikri scholars, especially this paper, deeply analyze the intellectual changes, political influences, and reform movements of this religious group in a historical context.